MORINDA TINCTORIA FRUIT ASSISTED BIOSYNTHESIS OF - R.KIRUBHA; G.ALAGUMUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Â Â Â Â Â Â Â Â Â Â Â Â Objective: To develop a reliable, eco-friendly and easy process for the synthesis of silver nanoparticles using fruit extracts of medicinal plant â€˜Morinda Tinctoria' and evaluate its anti-microbial properties. Methods: The synthesis and characterization of silver nanoparticles was confirmed by UVâ€“Visible, FR-IR, SEM, TEM, CV techniques and Disc diffusion assay method was used to confirm the antibacterial activity of silver nanoparticles. Results: UV-visible spectrum of the aqueous medium containing silver nanoparticles showed a peak around 420.25nm. FTIR analysis confirmed reduction of Ag+ ions to Ag0 ions in synthesized silver nanoparticles.The SEM and TEM analysis showed the particle size between 17-25nm, and spherical in structure.The silver nanoparticles have shown bactericidal effect against E.Coli, Staphylococus aureus, Bascillus cereus, and Pseudomonas aeruginosa. Conclusions: The fruit extract of M.Tinctoria quickly reduces Ag+ to Ag0 and enhances synthesis of silver nanoparticles with anti-microbial activity. Â KEYWORDS: Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Nanoparticles;Â Morinda Tinctoria; TEM; Silver nanoparticle, Antibacterial activity;